2003
DOI: 10.1002/ejlt.200390000
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of the autoxidation of fats: substrates with conjugated double bonds

Abstract: This paper provides a kinetic evaluation of rate data on the oxidation of conjugated linoleic acid methyl esters published by Kern et al. almost 50 years ago. The results of the kinetic analysis suggest that the oxidation of pure substrates with conjugated double bonds in bulk starts with carbon-oxygen cross-linking causing oligomerization (degree of polymerization ≈3). The reaction then proceeds with simultaneous oligomerization and formation of monomeric cyclic peroxides. The oligomerization was described by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Because the formation of such products has a high energy barrier, the 1,2-and 1,4-addition reactions of oxygen are not plausible pathways for the formation of cyclic peroxides. Formation of these peroxides through splitting of oligomers as suggested by Brimberg & Kamal-Eldin (2003) seems more probable but remains to be confirmed. It could, for example, be envisioned that decomposition of a dimeric alkoxyl radical, formed by the unzipping of a trimeric addition product, might yield a bisepoxide and the subsequent rearrangement of this epoxide a 1,2-dioxine (Fig.…”
Section: Figure 21mentioning
confidence: 93%
See 3 more Smart Citations
“…Because the formation of such products has a high energy barrier, the 1,2-and 1,4-addition reactions of oxygen are not plausible pathways for the formation of cyclic peroxides. Formation of these peroxides through splitting of oligomers as suggested by Brimberg & Kamal-Eldin (2003) seems more probable but remains to be confirmed. It could, for example, be envisioned that decomposition of a dimeric alkoxyl radical, formed by the unzipping of a trimeric addition product, might yield a bisepoxide and the subsequent rearrangement of this epoxide a 1,2-dioxine (Fig.…”
Section: Figure 21mentioning
confidence: 93%
“…The data supports oxygen-carbon rather than carbon-carbon polymerization, and indicates that appreciable amounts of isolated transunsaturation resides in the polymer fraction. Empirical kinetic reassessment of the early data by Brimberg & Kamal-Eldin (2003) suggests that oligomers having an average of three monomers would be kinetically favoured at the beginning of the oxidation and that the extent of oligomerization increases with increased temperature. Recently, Luna et al (2007) confirmed the formation of polymeric products during autoxidation of Me 9c,11t-CLA and Me 10t,12c-CLA.…”
Section: Polymerization (Pathway A)mentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the production of hydroperoxides is dormant and becomes noticeable at induction period (l, 21 days with released tocopherol of 241 mmol/kg), after which their concentration increases rapidly with time ( Figure 3). This phenomenon is typical of lipid oxidation in oil-rich food with or without antioxidants (Brimberg & Kamal-Eldin, 2003;Zhu, Schaich, Chen, Chung, & Yam, 2012). The induction period or time for conjugated dines or hydroperoxides to arrive at certain low level is usually adopted as a shelf life.…”
Section: Resultsmentioning
confidence: 99%